2022
DOI: 10.1038/s41586-022-04954-0
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine subsystems that track internal states

Abstract: Food and water are rewarding in part because they satisfy our internal needs1,2. Dopaminergic neurons in the ventral tegmental area (VTA) are activated by gustatory rewards3–5, but how animals learn to associate these oral cues with the delayed physiological effects of ingestion is unknown. Here we show that individual dopaminergic neurons in the VTA respond to detection of nutrients or water at specific stages of ingestion. A major subset of dopaminergic neurons tracks changes in systemic hydration that occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 76 publications
3
48
0
Order By: Relevance
“…On a trial-by-trial basis, striatal DA release integrates benefit size and sunk cost. Motivation for rewards, in contrast, reflects a state that changes over slower time scales, consistent with recent work on hunger 40,41 , thirst 41,42 , and other internal homeostatic drives 43,44 . The striatal DA signals encoding reward are dampened when motivation is high and augmented when motivation is low.…”
Section: Discussionsupporting
confidence: 82%
“…On a trial-by-trial basis, striatal DA release integrates benefit size and sunk cost. Motivation for rewards, in contrast, reflects a state that changes over slower time scales, consistent with recent work on hunger 40,41 , thirst 41,42 , and other internal homeostatic drives 43,44 . The striatal DA signals encoding reward are dampened when motivation is high and augmented when motivation is low.…”
Section: Discussionsupporting
confidence: 82%
“…These data suggest that these regions conveying food and water deprivation each relay onto the same population in NAcc. Recent studies indicate several indirect projections from ARC or SFO possibly via insular cortex, ventral tegmental area, or lateral amygdala ( 21 23 ). While distinct pathways lead to food or water intake, there is also evidence that these behaviors are interrelated as it has been observed that feeding and drinking are highly associated during meals in humans ( 3 ), raising the possibility that there may be neural mechanisms that coregulate and link feeding and drinking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that sensory signals activate ventral tegmental area dopamine neurons to mediate reward and that this activation occurs both before and after the consumption of sucrose as well as in response to other learned stimuli that are associated with goal acquisition ( 4 , 6 , 25 27 ). While our study examined neural dynamics of dopamine-receptor-expressing neurons in NAc during the sensory vs. oral phase, a recent study suggests that gastrointestinal (GI) infusions of nutrients vs. water activate distinct subsets of dopaminergic neurons in the VTA ( 22 ). This raises the possibility that oral phase and gastrointestinal phases engage distinct circuit elements in response to food vs. water.…”
Section: Discussionmentioning
confidence: 99%
“…The dopamine system is well-known to respond directly to food rewards and modulate food-seeking behaviors by acting in prefrontal and subcortical regions (Hajnal and Norgren, 2001 ; Bassareo et al, 2002 ; Hajnal et al, 2004 ; Berridge, 2007 ; Avena et al, 2008 ; de Araujo et al, 2010 ; Kenny, 2011 ; McCutcheon, 2015 ; Alhadeff et al, 2019 ; Zimmerman and Knight, 2020 ; Grove et al, 2022 ). Similarly, eCBs are tightly linked to feeding as they are derived from poly-unsaturated fatty acids and are able to modulate homeostatic and non-homeostatic/hedonic feeding (Mahler et al, 2007 ; Maccarrone et al, 2010 ; Lau et al, 2017 ; Coccurello and Maccarrone, 2018 ).…”
Section: Vulnerability Of Prefrontal Circuits During Adolescencementioning
confidence: 99%